A Denial-of-Service Attack Based on Selfish Mining and Sybil Attack in Blockchain Systems - Jing Zhang; Chunming Zha; Qingbin Zhang; Shaohua Ma (IEEE Access)
In the field of blockchain security research, especially regarding the core Proof of Work (PoW) consensus mechanism, researchers continue to reveal novel methods of mining attacks. Recently, Wang et al. demonstrated an innovative attack mode: the Selfish Mining-based denial of service (SDoS) attack, revealing how this attack strategy introduces a new threat to the blockchain system through the selfish mining strategy. Expanding upon Wang et al.’s findings, our research refines the mining strategy by integrating the strategy of Equal-Fork Stubborn Mining, a more sophisticated variant of selfish mining that can significantly enhance the attacker’s advantage under certain network conditions. Furthermore, we combine this refined strategy with a Sybil attack aimed at disrupting the normal propagation and confirmation processes of blocks within the blockchain system, effectively reducing the income of honest miners. Therefore, we propose a new mining attack – a denial of service (SSDoS) attack based on selfish mining and sybil attack. Our experimental results indicate that compared to other known mining attacks, the implementation of the SSDoS attack by an attacker drastically reduces the willingness of honest miners to continue their mining activities, leading to a significantly lower level of participation. For an honest miner controlling 10% of the total computational power, the portion of the critical profitability factor calculated in SSDoS that is higher than the one calculated in SDoS accounts for about 25%.